Effects of myocardial perfusion abnormalities on the accuracy of left ventricular volume and ejection fraction measured by thallium-201 gated single-photon emission tomography. Issue 11 (November 2015) - Kurisu, Satoshi; Iwasaki, Toshitaka; Abe, Nobukazu; Tamura, Megumi; Ikenaga, Hiroki; Watanabe, Noriaki; Higaki, Tadanao; Shimonaga, Takashi; Ishibashi, Ken; Dohi, Yoshihiro; Fukuda, Yukihiro; Kihara, Yasuki
<x xml:space="preserve">Abstract</x> Background We assessed the accuracy of left ventricular end-diastolic volume (EDV), end-systolic volume (ESV), and ejection fraction (EF) using quantitative gated single-photon emission computed tomography (QGS) in comparison with echocardiography as the reference standard. We also assessed the effects of total perfusion deficit (TPD) on the accuracy of QGS measurements. Methods A total of 258 patients underwent single-photon emission computed tomography and transthoracic echocardiography within 4 weeks of each investigation for evaluating coronary artery disease. Patients were divided into four groups according to TPD scores. Results There were 138 patients with no/minimal TPD, 64 patients with small TPD, 35 patients with middle TPD, and 21 patients with large TPD. There were good correlations and agreements in EDV (r=0.87, 0.90, 0.71, and 0.94, respectively), ESV (r=0.92, 0.94, 0.79, and 0.94, respectively), and EF (r=0.61, 0.79, 0.61, and 0.83, respectively) between QGS and echocardiography in patients with any TPD. QGS significantly underestimated EDV and ESV in patients with no/minimal or small TPD, and significantly overestimated ESV in patients with large TPD. QGS significantly underestimated EF in patients with middle or large TPD. Conclusion Our results suggest that QGS is a useful tool for assessing the left ventricular volume and function in patients with any TPD, but myocardial perfusion abnormalities should be taken into consideration when interpreting QRS measurements.